Pectin-Tannic Acid Nano-Complexes Promote the Delivery and Bioactivity of Drugs in Pancreatic Cancer Cells - Sumeet S. Chauhan; Advait B. Shetty; Elham Hatami; Pallabita Chowdhury; Murali M. Yallapu (MDPI AG, 2020)
Pancreatic cancer (PanCa) is a lethal disease. Conventional chemotherapies for PanCa offer severe systemic toxicities. Thus, the development of a successful nanomedicine-based therapeutic regimen with augmented therapeutic efficacy is highly sought. Naturally occurring pectin and modified pectin-based drug delivery systems exhibit remarkable self-targeting ability via galactose residues to various cancer cells. Herein, we developed and used an innovative approach of highly stable nanocomplexes based on modified pectin and tannic acid (MPT-NCs). The nanocomplex formation was enabled by strong intermolecular interactions between pectin and tannic acid under very mild conditions. These nanocomplexes were characterized by particle size and morphology (DLS, TEM, and SEM), FT-IR spectroscopy, and zeta potential measurements. Additionally, MPT-NCs were capable of encapsulating anticancer drugs (5-fluorouracil, gemcitabine, and irinotecan) through tannic acid binding. The in vitro bioactivity of these drug MPT-NCs were evaluated in pancreatic cancer adenocarcinoma (PDAC) cell lines (HPAF-II and PANC-1). A dose-dependent internalization of nanocomplexes was evident from microscopy and flow cytometry analysis. Both proliferation and colony formation assays indicated the anticancer potential of pectin drug nanocomplexes against PDAC cells compared to that of free drug treatments. Together, the pectin-based nanocomplexes could be a reliable and efficient drug delivery strategy for cancer therapy.